Development of a criterion for predicting residual strength of composite structures damaged by impact loading - Medeiros, Ricardo de (2016)
Advanced aerospace materials, including fibre reinforced polymer and ceramic matrix composites, are increasingly being used in critical and demanding applications, challenging not only the current damage prediction, detection, and quantification methodologies, but also the residual life of the structure. The main objective of this work consists of developing theoretical and experimental studies about residual strength for composite structures, which are damaged by impact loading, aided by a SHM system, which combines different methods. For this, it is necessary: to identify, and to localize damage, as well as to calculate the severity of the damage and to predict the residual strength of the composite structure. To achieve these goals, the research methodology should consider three methods: (1) Vibration Based Method (VBM); (2) Shearography Speckle (SS) and (3) Flexural After Impact (FAI). Composite plates, made of epoxy resin reinforced by carbon or glass fibre, are evaluated. Firstly, VBM provide Frequency Response Functions to be analysed by suitable metrics (including a new metric), which are compared in terms of their capability for damage identification and global location. Afterwards, the extension of impact damage is determined by using shearography speckle. This technique has demonstrated great potential for damage detection in composite laminated structures. The identification of the damage from the measurements performed with the SS technique is based on the analysis of disturbances in the speed field caused because of the different properties of the material. These abnormal deformations can be verified as typical strains in damaged structures. SS is a laser interferometry method sensitive to displacement gradient in a surface direction out of the plane. Under the action of a smaller load, the structure is deformed and the presence of damage is shown through local peculiarities of surface deformation observed field. Finally, a flexure after impact (FAI) test is used to evaluate its limitations and potentialities as a damage tolerance technique. The residual flexural strength of damaged specimens is evaluated by quasi-static four-point bending test. A new criterion based on a relationship between damage metric from VBM and FAI analysis is presented and discussed. Thus, these results are normalized by using the maximum load and the metrics for damage analyses, i.e. if there is no damage in the structure, then the metric returns zero value. If the structure is partially damaged then the metric returns a number between one and zero. In addition, if the structure is totally damaged (i.e. residual strength is lower than specified in design), then the metric returns a value equal one. Finally, it is discussed the advantages and limitations of this combination into the context of SHM system (Structural Health Monitoring System).